2018
DOI: 10.1530/joe-17-0709
|View full text |Cite
|
Sign up to set email alerts
|

The delayed effects of antibiotics in type 2 diabetes, friend or foe?

Abstract: An increasing amount of evidence suggests that the delayed effect of antibiotics (abx) on gut microbiota after its cessation is not as favorable as its immediate effect on host metabolism. However, it is not known how the diverse abx-dependent metabolic effects influence diabetic subjects and how gut microbiota is involved. Here, we treated db/db mice with abx cocktail for 12 days and discontinued for 24 days. We found that db/db mice showed decreased body weight and blood glucose after abx treatment, which ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…16S ribosomal RNA gene sequencing of the gut microbiota and quantification of bacterial DNA Bacterial DNA was extracted from colon content and faeces of mice as previously reported [25] and subjected to PCR amplification and Illumina MiSeq sequencing (San Diego, CA, USA). See ESM Methods for more details.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16S ribosomal RNA gene sequencing of the gut microbiota and quantification of bacterial DNA Bacterial DNA was extracted from colon content and faeces of mice as previously reported [25] and subjected to PCR amplification and Illumina MiSeq sequencing (San Diego, CA, USA). See ESM Methods for more details.…”
Section: Methodsmentioning
confidence: 99%
“…Triacylglycerol and cholesterol measurement Triacylglycerol and total cholesterol in both liver and plasma of mice were measured by the Quantification Colorimetric/Fluorometric Kit (Biovision, Milpitas, CA, USA), as previously reported [25]. See ESM Methods for further details.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we observed that a portion of pig-derived microbes capable of degrading indigestible carbohydrates leading to the production of short-chain fatty acids (SCFAs), including Bacteroidetes [45], Prevotellaceae [46], and some families of Firmicutes such as Veillonellaceae [47], Lachnospiraceae [48], and Ruminococcaceae [49], had a greater preference to invade the recipient LI relative to the recipient SI. Families Erysipelotrichaceae and Mogibacteriaceae under the phylum Firmicutes, which are designated as "obesity" bacterial taxa positively correlated with the production of secondary bile acids [50][51][52], also exhibited greater relative densities in the recipient LI receiving the introduction of exogenous large-intestinal communities than those in the recipient SI. Microbes within Erysipelotrichaceae were also positively correlated with a number of parameters involved in carbohydrate digestion including dietary carbohydrate and fiber content and SCFAs production while negatively correlated with fat digestibility and protein metabolism [53][54][55].…”
Section: Niche-specific Colonization Of Exogenous Microbiota Across Dmentioning
confidence: 99%
“…Furthermore, the resistome in disease states is largely unexplored. Antibiotic intervention influences some phenotypes closely related to the gut microbiome, such as metabolic disorders ( Yang et al, 2017 ; Fu et al, 2018 ), immunopathologies ( Wypych and Marsland, 2018 ), cancer ( Cao et al, 2018 ; Zhang et al, 2019 ), and hypertension. Thus, it is worthwhile to explore the characteristics of ARGs in disease states and its association with bacteria, which may provide a new perspective for the identification of disease markers.…”
Section: Introductionmentioning
confidence: 99%